2014
DOI: 10.1002/smi.2591
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism Affects Blood Pressure in Response to Repeated Exposure to Stress

Abstract: This pilot study examined the effects of perfectionism on blood pressure (BP) in response to repeated exposure to mental arithmetic stressors. College students (N = 30) in a laboratory setting were administered a series of challenging mathematical tasks. BP was measured at baseline and after each task. Multilevel modelling analyses revealed that BP tended to decline over the course of the mathematical tasks. However, higher levels of performance standards predicted relatively stable levels of systolic BP, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Several researchers suggest that perfectionism links to somatic problems such as migraine headaches (see Bottos & Dewey, ; Burns, ; Stout, ; Wolff, ), hypertension and cardiovascular illnesses (Albert, Rice, & Caffee, ; Shanmugasegaram et al, ), gastrointestinal illnesses (Flett, Baricza, Gupta, Hewitt, & Endler, ), asthma (Kristiansen, Abrahamsen, & Stensrud, ), and chronic pain (Hadjistavropoulos, Dash, Hadjistavropoulos, & Sullivan, ). Relatedly, Molnar et al () asserted that socially prescribed perfectionism is associated with a range of ill health symptoms (i.e., sleep problems, shortness of breath, upset stomach, fatigue, pains, and ailments).…”
Section: The Influence Of Perfectionism On Emotions Cognition Behavmentioning
confidence: 99%
“…Several researchers suggest that perfectionism links to somatic problems such as migraine headaches (see Bottos & Dewey, ; Burns, ; Stout, ; Wolff, ), hypertension and cardiovascular illnesses (Albert, Rice, & Caffee, ; Shanmugasegaram et al, ), gastrointestinal illnesses (Flett, Baricza, Gupta, Hewitt, & Endler, ), asthma (Kristiansen, Abrahamsen, & Stensrud, ), and chronic pain (Hadjistavropoulos, Dash, Hadjistavropoulos, & Sullivan, ). Relatedly, Molnar et al () asserted that socially prescribed perfectionism is associated with a range of ill health symptoms (i.e., sleep problems, shortness of breath, upset stomach, fatigue, pains, and ailments).…”
Section: The Influence Of Perfectionism On Emotions Cognition Behavmentioning
confidence: 99%
“…Maladaptive perfectionists show the opposite physiological profile. For example, systolic blood pressure, used as a measure of vagal tone, was found to be stable over the course of difficult tasks for perfectionists, while it declined for those with lower levels of standards (Albert, Rice, & Caffee, 2014;Besser, Flett, Hewitt, & Guez, 2008).…”
Section: Emotion Regulationmentioning
confidence: 99%
“…This pattern of results is also in line with prior results that frequently indicated that perfectionistic concerns are a stronger predictor of distress than perfectionistic strivings are on the level of dispositional perfectionism (see Stoeber & Gaudreau, 2017) and on the level of perfectionistic cognitions (Prestele & Altstötter‐Gleich, 2019a). However, these findings might not hold for all kinds of criterion variables (e.g., positive affect; Stoeber et al, 2010) or all situations (e.g., repeated failure; Albert, Rice, & Caffee, 2016). Future studies might systematically investigate the predictive validity of between‐person differences in PSC beyond PCC across positive and negative criterion variables and across different situations (e.g., situations with a more direct focus on potential gains).…”
Section: Discussionmentioning
confidence: 97%